Contemporary analysis of otolaryngic allergy. (14th April 2019) - Harrill, Willard C.; Setzen, Gavin; Farquhar, Douglas; Pillsbury, Harold C.
Abstract : Objectives: Investigate the current trends in otolaryngic allergy (OA). Study Design: Cross‐sectional survey. Methods: Survey of active AAOA membership. Results: Response rate was 27.3%. Regional response distribution rates were proportional to the AAOA membership distribution within the United States (R2 = 0.95; P < 0.001), with no significant regional response bias demonstrated ( P = 0.428). Self‐reported duration to OA competency was 5.8 years. Physicians reporting OA competency were more likely to be board‐certified ( P < 0.001) and have AAOA fellowship status ( P < 0.001). The AAOA was reported to be the most valuable educational resource toward achieving OA competency, with residency training being least valuable ( P < 0.001). 91.5% of respondents' practices offered OA services. Subcutaneous injections predominated at twice the utilization of sublingual immunotherapy. Allergy immunotherapy tablets were rarely utilized. Home allergy shots were offered by 45.2% of respondents. In‐office immunotherapy vial compounding was preferred (95.8%) to third‐party vendors. 94% of AAOA respondents identified patient compliance to be an issue within OA. Non‐inhalant allergy service integration included food allergy (63.5%), asthma (44.9%), allergic fungal sinusitis (43.8%), penicillin allergy (18%), stinging insect allergy (12.6%), and aspirin desensitization (3.9%). Conclusion: Reported duration to OA competency after residency was surprisingly long. Further investigation of current and future educational/clinical training is warranted given clinical integration reported for OA. Otolaryngology is in the unique position to develop a comprehensive sino‐allergy evidence‐based strategy integrating the extensive diagnostic and medical treatment arms alongside the surgical expertise of the specialty within a clinical sino‐allergy home concept. Level of Evidence: 5 Laryngoscope, 130:283–289, 2020